The effects of selected lifestyle components on the risk of developing dynapenia in women – a pilot study - Bogucka, Aleksandra; Kopiczko, Anna; Głębocka, Anna (Anthropological Review, 2018)
Aging processes in a body inevitably lead to changes which may decrease the quality of life of the elderly. Dynapenia is a phenomenon which is still not well known and needs to be studied in the population. The aim of the research was to determine the effects of lifestyle on the risk of developing dynapenia in post-menopausal women. The study included 46 females aged 71.4 ±5.6 living in the town of Wysokie Mazowieckie. Basic body dimensions and body composition elements were assessed with the use of anthropometry and bioelectrical impedance analysis (BIA). A direct interview method with the use of the modified Sedentary Behavior Questionnaire (SBQ) was applied. In order to assess the prevalence of dynapenia, handgrip strength was measured with the use of hydraulic dynamometer. Physical activity was assessed with the use of a pedometer. The respondents’ nutrition was examined in an interview concerning their diet from the 24 hours preceding the examination according to the methodology of Food and Nutrition Institute (FNI). The intake of energy and nutritional elements in a diet was calculated with using DIETA 5.0 computer software. Dynapenia was diagnosed in 21.7% of the examined women. The women with dynapenia had significantly bigger waist and hip circumferences and higher BMI (p<0.05) as well as significantly weaker hand muscles than healthy women (p<0.001). Females with dynapenia spent significantly more time in a sedentary position, i.e. talking on the phone, participating in religious rituals or watching TV (p<0.05) compared to women without dynapenia. No significant differences concerning the diet of women with and without dynapenia were revealed. Physical activity may significantly decrease the risk of dynapenia among women over 60 years of age. Furher research is needed to assess the risk of dynapenia and methods of its prevention.